Sistem Kontrol Kelembaban Tanah dan Penyiraman Otomatis Pada Tanaman Seledri (Apium graveolens L.) Yang Dipengaruhi Oleh Suhu Berbasis Mikrokontroler - Ghina Athaya Adhana; Rahmat Rasyid (Jurnal Fisika Unand, 2024)
A system of soil moisture control and automatic watering has been designed for celery (Apium graveolens L.) which is influenced by temperature and humidity based on a microcontroller. This system functions to water the plants automatically based on the soil moisture that has been set in the program. The system will provide information to the user when the soil moisture is more than 75%. The system consists of a DHT11 sensor as a temperature and humidity detector, a capacitive soil moisture sensor to detect soil moisture, a relay as a mini water pump switch for watering plants, red and green LEDs as indicator lights according to the measurement results of a capacitive soil moisture sensor and LCD. to display temperature, air humidity and soil moisture. The test results show that the tool can function properly, if the soil moisture is <75% the pump will start and the soil moisture ≥75 the pump will stop so that watering does not occur. The highest humidity obtained was 83% and the lowest temperature was 23°C with the condition that the plants did not look dry, while the highest temperature obtained was 30°C and the lowest humidity was 77% with the conditions that the plants looked dry.